Modal analysis for micro-end milling machine tools - Tan, Kai Chao. (2010)
This report details the modal analysis tests of micro-end milling machine tools. Modal testing is a form of vibration testing, which is able determine the frequency response function (FRF) of the mechanical test structures. However, the challenge present is that the conventional methods of exciting a test structure, for example impact hammer excitation, cannot be applied onto micro-end milling tools. This is due to their small diameter and brittleness, thus it is not possible to excite the micro-end milling tools accurately and without breaking them. The author’s approach to solve the problem is through the use of the receptance coupling method. In this method, the micro-end milling system is divided into two substructures, the spindle part and the tool part. The FRF of the tool is determined analytically by finite element analysis (FEA), due to physical constraints of a micro-end milling tool, while the FRF of the spindle is determined experimentally by impact hammer testing. The receptance coupling technique is able to combine the modal parameters of the substructures and obtain the overall FRF of the whole assembly. The author begins by performing the impact hammer test on a simple cantilever beam, and obtaining its FRF with the help of a Matlab programme.FEA is performed on the same cantilever beam, and the results compared with those from the impact hammer test to verify the accuracy of the Matlab programme. Impact hammer test will then be carried out on an actual milling machine and FEA on an actual micro-end mill tool. Finally, the receptance coupling method is discussed.